Comparative economic analysis of cucumber under different protected structures - Parveen, Kumar Nimbrayan; Parminder, Singh; Avinash, Kumar; Sharad, Sachan; Sood, Shivalika (Plant Science Today, 2025)
An economic analysis was conducted to assess cucumber production under different protected structures naturally ventilated polyhouses (NVPH), net houses and walk-in tunnels in Sonepat, Karnal and Hisar districts of Haryana. The study revealed notable differences in profitability and efficiency across districts and structures. NVPH cultivation was most profitable in Sonepat, which also exhibited the highest benefit-cost ratio, followed by Karnal and Hisar. In net houses, Karnal outperformed the other districts in both net returns and benefit-cost ratio, with Sonepat ranking second and Hisar third. For walk-in tunnels, Sonepat again recorded the highest net returns and benefit-cost ratio, while Hisar showed comparatively lower profitability. These findings suggest that district-specific and structure-specific management practices have a significant impact on economic outcomes in cucumber cultivation. The marketing analysis highlighted that the share of the consumer’s rupee reaching the producer varied across districts. Channel III, which involves direct sales from producer to consumer, was most beneficial in Hisar, allowing producers to capture a larger share, followed by Sonepat and Karnal. Overall, the study emphasizes the importance of selecting appropriate protected structures based on district conditions and marketing channels to maximize returns and efficiency in cucumber production.